y = mx + b y = 0.666666666666666666667(x) + 6 m = slope b = y intercept
It is in slope intercept form. The slope is 0 and the y-intercept is -2.
The y intercept is when x =0, so the answer is -6
-3
x - 9y = 18At the x-intercept, y=0 :x = 18At the y-intercept, x=0 :-9y = 18-y = 2y = -2
36
6x - 3y = 36 x intercept: If y = 0, then 6x=36 so x=6 y intercept: If x = 0, then -3y=36 so y = -12
The y-intercept equals 0.
Slope and y-intercept of y equals 2.5x is: Slope is 2.5 and y-intercept is 0
The equation you gave (-9x - 36 = 6x) does not have y included anywhere. Assuming you meant that -9x - 36 = 6x + y: Step 1: Give y its own side: -9x - 36 -6x = 6x - 6x + y -15x -36 = y Step 2: Set x as 0 -15(0) - 36 = y y = -36 The y-intercept is -36
I assume you mean. 4X - 3Y = -36 subtract 4X from each side -3Y = -4X -36 divide both sides by -3 Y = 4/3X + 12 12 is Y intercept
6x - 5y = 36At the x-intercept, y=0.6x = 36x = 6
At the x-intercept, y = 0 So the equation becomes 4x = -36 or x = -9 So the x-intercept is (-9, 0)
I think they will intercept
The y intercept is -6
The intercept is [ y = 7 ] .
The y intercept is 1